2015
DOI: 10.1093/nar/gkv1519
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome-wide effects of vitamin D and their impact on the transcriptome of human monocytes involve CTCF

Abstract: The physiological functions of vitamin D are mediated by its metabolite 1α,25-dihydroxyvitamin D3 (1,25(OH)2D3) activating the transcription factor vitamin D receptor (VDR). In THP-1 human monocytes we demonstrated epigenome-wide effects of 1,25(OH)2D3 at 8979 loci with significantly modulated chromatin accessibility. Maximal chromatin opening was observed after 24 h, while after 48 h most sites closed again. The chromatin-organizing protein CTCF bound to 14% of the 1,25(OH)2D3-sensitive chromatin regions. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
122
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(132 citation statements)
references
References 57 publications
4
122
0
1
Order By: Relevance
“…human monocyte cell culture model [18]. As expected, the vitamin D 3 dose increased the vitamin D status of the study participants, as measured by 25(OH)D 3 serum levels, within one day by some 20%.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…human monocyte cell culture model [18]. As expected, the vitamin D 3 dose increased the vitamin D status of the study participants, as measured by 25(OH)D 3 serum levels, within one day by some 20%.…”
Section: Discussionsupporting
confidence: 76%
“…The first effect of activating VDR by its ligand is a transient opening or closing of chromatin at specific enhancer and transcription start site (TSS) regions that results in a second step in the activation or repression of vitamin D target genes, such as cathelicidin antimicrobial peptide (CAMP) or PTH, respectively [15]. In THP-1 human monocytic leukemia cells we have demonstrated that the method formaldehyde-assisted isolation of regulatory elements (FAIRE) [16] is well suited to monitor vitamin D-modulated changes in chromatin accessibility [17,18]. This means that vitamin D stimulation of cultured cells, and probably also of human tissues and cell types in vivo, results in changes of the epigenome.…”
Section: Introductionmentioning
confidence: 99%
“…To date, epigenetic effects by vitamin D have primarily been associated with histone modifications, and it is well known that binding of vitamin D to VDR/RXR induces conformational changes that favor release of corepressors and interaction with coactivators and histone acetyltransferases (21,22). Indeed, a recent study using FAIRE-seq in a monocytic cell line demonstrated that vitamin D affects chromatin accessibility at nearly 9,000 sites in the genome (39). The most pronounced effect was observed early after VDR/RXR engagement, causing opening of the chromatin with CCCTC-binding factor (CTCF) being likely involved in this early reprograming.…”
Section: Discussionmentioning
confidence: 99%
“…The type of VDR/RXR-interacting proteins suggests that vitamin D can induce both gene activation and repression (21). Although early response to vitamin D in a monocytic cell line is characterized by activation of gene expression, late response is characterized by the closing of the affected chromatin and similar proportion of up-and down-regulated genes (39). Equal proportion of up-and down-regulated genes has also been described in primary T cells after 10 d of exposure to a vitamin D analog (51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation